Physical and chemical properties of particleboard made of rice straw and plastic waste. (February 2020) - Fitri, N; Mursal; Ismail, I
Abstract: Rice straw is agricultural waste which hasn't been used optimally yet, especially in Indonesia. Meanwhile, rice straw contains cellulose that can be used form composite such particleboard. In this study, the physical and chemical properties of particleboard made of rice straw particle and polypropylene from plastic waste as adhesive were investigated. The rice straw and polypropylene compositions were varied: 30:70, 40:60, 50:50, and 60:40 wt.%. The rice straw particle sizes were varied for 40 mesh, 50 mesh, and 60 mesh for each composition. X-Ray Fluorescent has been used to measure the chemical composition of our particleboard. The density of particleboard is 0.59-0.77 g / cm 3 . Its thickness swelling is less than 2%. Both density and thickness swelling has met the requirement for Indonesian Standard of particleboard. Our results showed that the density of particleboard strongly depends on rice straw particle size. As the particle size decreases, the density increases. The particle size of rice straw affects the thickness swelling of particleboard. The thickness swelling decreases as the particle size decreases. The major constituents of our particleboard are the SiO2, CaO, K2 O. Our finding showed that the particle size has an essential role in the physical properties of particleboard.